2013
DOI: 10.1371/journal.pone.0077586
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Niemann-Pick Type C2 Protein Expression in Multiple Cancers Using a Novel NPC2 Monoclonal Antibody

Abstract: Niemann-Pick Type C2 (NPC2) plays an important role in the regulation of intracellular cholesterol homeostasis via direct binding with free cholesterol. However, little is known about the significance of NPC2 in cancer. In this study, we have pinpointed the impact of various different cancers on NPC2 expression. A series of anti-NPC2 monoclonal antibodies (mAbs) with the IgG2a isotype were generated and peptide screening demonstrated that the reactive epitope were amino acid residues 31-40 of the human NPC2 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…The specificity and immunoreactivity of NPC2 mAbs were assessed using Western blot and IHC staining, respectively. 36 In this study, we further demonstrate that downregulation the protein level of NPC2 in HCC patients is associated with higher a-fetoprotein, multiple tumor type, vascular invasion, later pathological stage and shorter survival rate ( Fig. 1 and Table 2).…”
Section: Discussionsupporting
confidence: 69%
“…The specificity and immunoreactivity of NPC2 mAbs were assessed using Western blot and IHC staining, respectively. 36 In this study, we further demonstrate that downregulation the protein level of NPC2 in HCC patients is associated with higher a-fetoprotein, multiple tumor type, vascular invasion, later pathological stage and shorter survival rate ( Fig. 1 and Table 2).…”
Section: Discussionsupporting
confidence: 69%
“…Perturbations of cholesterol metabolism affect cancer progression [ 33 ]. Elevated serum levels of NPC2 have been observed in patients with lung cancer [ 34 ] and, more recently, HCC [ 35 ]. Modulation of cholesterol homeostasis by NPC2 also affects activation of mammalian target of rapamycin (mTOR) [ 36 ], a critical signaling cascade in several types of cancer including HCC [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…In-vitro and in vivo xenograft data demonstrated that the expression of NPC2 regulates cell proliferation, migration, and tumorigenesis by regulating ERK1/2 activation [ 21 ]. Previously, we conducted an immunohistochemical-based study to examine the expression of NPC2 in a variety of different human cancers, and meanwhile NPC2 was found to be down-regulated in human liver cirrhosis and hepatoma tissues [ 22 ]. However, the molecular mechanisms of NPC2 in HSCs activation and liver fibrosis have not been explored in detail.…”
Section: Introductionmentioning
confidence: 99%